2016
DOI: 10.1155/2016/5982397
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Damage Mechanism Related to CO2Laser Cochleostomy on Guinea Pig Cochlea

Abstract: Different types of lasers have been used in inner ear surgery. Therefore, it is of the utmost importance to avoid damage to the inner ear (e.g., hyperthermia and acoustic effects) caused by the use of such lasers. The aim of this study was to use a high powered fibre-enabled CO2 laser (10 W, 606 J/cm2) to perform cochleostomies on guinea pig cochlea and to investigate the possible laser-induced damage mechanisms. The temperature changes in the round window membrane, auditory evoked brainstem response, and morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In addition, striatin has been shown to colocalize with β-catenin, a junctional protein, in different tissues ( Domke et al, 2014 ; Franke et al, 2015 ; Domke and Franke, 2019 ). However, as our previous studies indicate that in the mammalian cells tested striatin did not bind or colocalize with β-catenin ( Breitman et al, 2008 ) and that in the inner ear β-catenin is barely seen in hair cells ( Liu et al, 2016 ), the possibility that striatin and β-catenin interact was not examined in the current study. Another interesting prospect is the effect of striatin on proto-cadherins.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, striatin has been shown to colocalize with β-catenin, a junctional protein, in different tissues ( Domke et al, 2014 ; Franke et al, 2015 ; Domke and Franke, 2019 ). However, as our previous studies indicate that in the mammalian cells tested striatin did not bind or colocalize with β-catenin ( Breitman et al, 2008 ) and that in the inner ear β-catenin is barely seen in hair cells ( Liu et al, 2016 ), the possibility that striatin and β-catenin interact was not examined in the current study. Another interesting prospect is the effect of striatin on proto-cadherins.…”
Section: Discussionmentioning
confidence: 77%
“…Liu at al., analyzing the increase in the temperature of the round window in guinea pigs and the change in auditory evoked potential by exposure to a CO 2 laser at an intensity of 10 W, 3-mm of distance at a cochleostomy, they found an increase of 8 °C, which was enough to induce hearing loss and in the histological study of these guinea pigs, they found damage to outer hair cells. 13 This shows that little increase of temperature damages cochlear hair cells with hearing loss in animals. We consider that our work provides important information to raise awareness about the possibility of injury to the inner ear when using a 4-mm rigid endoscope in otological surgeries, especially for a longer period of time and with the tip of the endoscope close to the round window.…”
Section: Discussionmentioning
confidence: 96%